Ultrassonografia abdominal de tamanduás-bandeira (Myrmecophaga tridactyla) machos e fêmeas - Albuquerque, Luíza Lucena de (2017)
The giant anteater (Myrmecophaga tridactyla) is a wild mammal of the superorder of Xenarthras, native to Central and South America, which is currently classified as vulnerable in the list of endangered species. A fact that can have as causes, from the territorial advance of the agricultural activities to the constructions of roads and fires. Scientific research is of great importance for the conservation of species included in this list and there is a dearth of data about the anteater. Among these information to be collected, there is little information about ultrasound examination in this species. The absence of a reference standard for performing and evaluating ultrasonographic examination for specific species may limit the application of this test and disrupt the establishment of an accurate diagnosis. For these reasons, the aim of this study was to establish a reference standard for the ultrasonographic evaluation of the abdomen of male and female giant anteaters. For this, 10 adult animals, five females and five males, clinically healthy, were used from the Fundação Jardim Zoológico de Brasília. The animals were anesthetized using the Foundation's own protocol, the animals were placed in dorsal decubitus position, and then a wide tricotomy of the abdomen was performed to allow abdominal scanning. The visible structures were established in the abdominal ultrasound examination of the anteaters, have also been established: topographic position, anatomical relationships, ecotexture and echogenicity of: urinary vesicle, uterus, testes, kidneys, spleen, liver, stomach and intestines. It has also been described the presence of alterations in some animals, such as: an animal with intrauterine fluid; an animal with hepatomegaly; an animal with splenomegaly; and thre animals with abdominal fluid. It has been verified that the abdominal ultrasound examination of anteater can be performed according to what is already recommended for dogs and cats and its evaluation and interpretation can be compared with the examinations of domestic mammals as well as descriptions already documented in other species of mammals Wild.